Effectiveness of problem-based learning-teaching algebra among form four students - Kalaivani, Katherine (2011)
The purpose of this study is to examine the effectiveness of problem-based learning (PBL) in teaching algebra among Form Four students. The study consisted of 81 students from two classes of a government school, 4 Setia (n=41) as the experimental group and 4 Mulia (n=39) as the control group. Using the quasi-experiment of posttest-only control group design, 6 lessons of teaching using PBL and traditional approach was carried out with a total of 16 teaching period in each. The instruments used were the performance test, assessment exercises and student engagement survey. Data obtained from the performance test were analyzed using the non-parametric statistics (Mann-Whitney U Test) as the shape of the data distribution of population was not normal. It is observed that the experimental group in which the PBL approach was applied performed better than the control groups to which traditional teaching approach was applied in the overall performance in algebra and performance in algebra higher-order thinking (HOT) questions. Mean and standard deviation was used to generalize the engagement of students toward learning algebra using the PBL approach. In general, the students were found to be positively engaged in learning algebra when taught using the PBL approach. Also, a non-parametric statistical analysis (Spearman’s Rank Order Correlation) was used to understand the relationship between student engagement and the overall performance in algebra. There was a medium and positive correlation found between the two variables. In conclusion, the study shows that PBL is an effective instructional methodology tool in enhancing students’ HOT skills and increasing engagement toward learning algebra.